Enhancing integrated transport planning: A spatial multi-criteria analysis approach to the MyCiTi integrated rapid transit system, South Africa - Barendse, Caro-Joy (Department of Civil Engineering, 2017)
Since the birth of the automobile in 1886, its popularity amongst people has risen dramatically owing to the freedom, comfort, speed, safety and unique designs offered by this mode of transport. 2014 saw approximately 71.15 million units of new vehicle sales globally, showing that private car usage is still on the rise. Rapid degradation of the environment and slumped economic growth can be attributed to the automobilecentric transport system. Raised environmental and social awareness has driven campaigns to promote greener modes of transport instead, such as public and nonmotorised transportation. This has seen the introduction of BRT systems in South African cities however; fully integrated transport systems are yet to be achieved. Thus there is a dire need for a design support tool that is adequately capable of processing built environment characteristics in the development of a BRT feeder network that is fully appreciative of the influence of NMT and the urban fabric, and is thus appropriate to the needs of the community it is trying to serve. This study comprised the application of two Spatial Multi-Criteria based methodologies in which a list of built environment characteristics and public transport demand formed the inputs for the analyses. The analysis produced a composite suitability map for each approach, in which each pixel represented the appropriateness of having a BRT feeder route located in that respective pixel. Routes between O-D pairs identified were solved by carrying out a least cost path assessment based on the mean impedance values along the existing road network. The routes developed were compared to the MyCiTi feeder bus routes using Key Performance Indicators established in this research to determine whether this study was successful in producing an enhanced BRT feeder route planning tool. Apart from one route, the set of feeder routes developed for each approach were exactly the same with the second method producing lower average impedance values per kilometre thus it was deemed stronger. When compared to the MyCiTi feeder routes, similar operational efficiencies were achieved with respect to average travel time, coverage and directness. However; the study methodologies provided a greater level of NMT planning inclusion and consideration of environmental factors. Furthermore; it achieved this in a systematic and transparent manner, providing immensely powerful benefits for transportation planners in the public sector. This study was successful in demonstrating that SMCA combined with the Network Analyst tool in ArcGIS has the ability to enhance the quality and appropriateness of BRT feeder routes, whilst achieving acceptable operational efficiencies. The results could further be improved by incorporating more data on local NMT trends and behaviour. Furthermore; this tool can be applied to solving pedestrian, bicycle and other public transport routing problems.